Identification of Doris verrucosa mollusc via mitochondrial 16S rDNA. (February 2015) - De Masi, L.; Adelfi, M.G.; Pignone, D.; Laratta, B.
Abstract: The biological and molecular knowledge of the marine life is of enormous importance in discovering new classes of natural products and in improving management and sustainable utilization of these useful genetic resources. Nonetheless, in this frame, genomic and organelle DNA isolation has been reported to be a limiting step, since downstream applications of molecular biology, such as restriction enzyme digestion, polymerase chain reaction (PCR) and DNA sequencing are hampered by the presence of compounds that are concurrently extracted. In this work we compared different DNA extraction techniques in three marine organisms and tested the downstream applications. One of the species utilized in this work was the Nudibranch Doris verrucosa L., a species with a well-known pharmaceutical interest. The phylogeny of this mollusc has long been discussed on the basis of morphological characters. As a result, D. verrucosa has often been misidentified with other sister species. Mitochondrial 16S rDNA sequence was chosen to better solve this concern and to accurately settle D. verrucosa into the right position. A partial sequence of the mt 16S rDNA of the Nudibranch D. verrucosa was obtained for the first time. The results here presented will provide knowledge useful to a better management and use of marine genetic resources, as well as in resolving taxonomic and identification issues currently open in these marine invertebrates. Highlights: The Nudibranch Doris verrucosa L. is well-known for its pharmaceutical interest. The phylogeny of D. verrucosa has long been discussed. An mt 16S rDNA fragment of the Nudibranch D. verrucosa was acquired for the first time. mt 16S rDNA sequence was used to clarify D. verrucosa misidentification doubts.